Comparing the effects of qur’an recitation and nature sounds on preoperative anxiety and physiological parameters among patients undergoing surgery at a teaching hospital - Rusli, Mohammad Farhan; Ismail, Mohd Nizamuddin; Abdul Hadi, Azwanis; Abd. Aziz, Karimah Hanim; Mohammad Aidid, Edre; Azli, Noraqila; Zulkifli, Najhan Anis; Mohd Zain, Uzair Idzwan Zain; Zainal Abidin, Nur Anisah (Kulliyyah of Allied Health Sciences, IIUM, 2019)
There is an increasing concern regarding the impact of sounds on the physiologic response of patients. Several studies observed the individual effects of Qur’an recitation and nature sounds on patients’ emotions and their physiological parameters. There was evidence of improvement seen among the studies conducted on patients undergoing surgery. Thus, this study aim is to compare the effectiveness of listening to Qur’an and nature sounds on preoperative anxiety and physiological parameters. A randomised controlled trial study using systematic random sampling was conducted at the International Islamic University Malaysia Medical Center (IIUMMC) in Kuantan, Pahang, Malaysia. A total of 81 patients are allocated to three equal groups which were a group that listened to Qur’an recitation or nature sounds for 20 minutes and a control group. Preoperative state anxiety was measured by using the Spielberger State-Trait Anxiety Inventory (STAI), and physiological parameters were recorded before and after the intervention. Data were analysed using repeated-measures ANOVA. There was an insignificant difference in all physiological parameters data observed between the two groups. The mean anxiety level of nature sounds group is significantly lower than that of the control group (p < 0.015) but no significant reduction observed after listening to Quran compared to control group (p = 0.165). An insignificant difference has been found in preoperative anxiety data between those who listened to Qur’an recitation and nature sounds (p=1.000). Listening to Quran recitation and nature sounds were found to be effective in reducing preoperative anxiety. Both Qur’an and nature sounds had similar effects on state anxiety score, and both showed a similar level of reduced preoperative anxiety. They can be used as a nonpharmacological intervention to reduce preoperative anxiety among patients undergoing surgery.